2022
DOI: 10.1186/s12905-022-01648-7
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban migration as a factor associated with physical and sexual intimate partner violence Peru 2015–2017: a secondary analysis of a national study

Abstract: Background Internal migration, a consequence of the demographic transition towards urbanization driven by globalization, represents a particular public health challenge. Change in residence from one sociocultural geographic context to another, with not only economic implications, but also changes in women’s long-established relationships of family interdependence, influences gender relations and can influence Intimate Partner Violence (IPV) against women. Different migratory trajectories may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This result spotlighted the rule of general practitioner doctors and pharmacists as basic sources of medical information in the Egyptian population which necessitate their training and increase their stroke awareness. This result is following the work of Terrazas and Blitchtein [11] who identified that earning for employed workers is more feasible in urban than rural areas with a consecutive large gap in income as well as the accessibility of medical services which may make many people vulnerable to migration pressure and leaving their homes in the countryside and migrate towards urban centers both within their own countries and across borders.…”
Section: Discussionsupporting
confidence: 66%
“…This result spotlighted the rule of general practitioner doctors and pharmacists as basic sources of medical information in the Egyptian population which necessitate their training and increase their stroke awareness. This result is following the work of Terrazas and Blitchtein [11] who identified that earning for employed workers is more feasible in urban than rural areas with a consecutive large gap in income as well as the accessibility of medical services which may make many people vulnerable to migration pressure and leaving their homes in the countryside and migrate towards urban centers both within their own countries and across borders.…”
Section: Discussionsupporting
confidence: 66%
“…There are three main types of labor migration. They are circular, permanent and commuting (Terrazas & Blitchtein, 2022).…”
Section: Introductionmentioning
confidence: 99%